2021
DOI: 10.3390/plants10122791
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutation in the Acetohydroxyacid Synthase (AHAS), Gene Confers Imidazolinone Resistance in Chickpea Cicer arietinum L. Plants

Abstract: Chickpea (Cicer arietinum L.) is an important crop in crop-rotation management in Israel. Imidazolinone herbicides have a wide spectrum of weed control, but chickpea plants are sensitive to acetohydroxyacid synthase (AHAS; also known as acetolactate synthase [ALS]) inhibitors. Using the chemical mutagen ethyl methanesulfonate (EMS), we developed a chickpea line (M2033) that is resistant to imidazolinone herbicides. A point mutation was detected in one of the two genes encoding the AHAS catalytic subunit of M20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Wheat and Chickpea cicer arietinum L. Plants. beans also won the IMI mutants in this way ( Chen et al., 2021 ; Galili et al., 2021 ).…”
Section: Recent Studies In Plants Using Ems Mutagenesismentioning
confidence: 99%
“…Wheat and Chickpea cicer arietinum L. Plants. beans also won the IMI mutants in this way ( Chen et al., 2021 ; Galili et al., 2021 ).…”
Section: Recent Studies In Plants Using Ems Mutagenesismentioning
confidence: 99%
“…In 2021, Galili et al demonstrated that imidazolinone herbicides manifest a broad spectrum of weed control, yet chickpea plants display sensitivity to acetohydroxyacid synthase (AHAS, also known as acetolactate synthase [ALS]) inhibitors. Through the utilization of the chemical mutagen ethyl methanesulfonate (EMS), a chickpea line (M2033) was generated, displaying resistance to imidazolinone herbicides [67].…”
Section: Achievements Of Mutation Breedingmentioning
confidence: 99%
“…Non‐ALS‐based resistance also exists in this species, 19,24,25,27,28 but is most often associated to mutant ALS alleles 24,25,29 . This makes poppy an excellent candidate for herbicide resistance diagnosis based on massive parallel ALS sequencing, all the more so as a number of studies in the domains of weed science, enzymology or crystallography have pinpointed at least 42 ALS codons with a proven or a possible role in sensitivity to ALS inhibitors 30–34 . Of those, nine proven determinants of resistance have been observed in weeds from the field (codons 122, 197, 205, 206, 376, 377, 574, 653 and 654; codon numeration is standardised to the Arabidopsis sequence as recommended), 35,36 12 have been reported in laboratory mutants (121, 124, 196, 199, 203, 256, 351, 352, 375, 570, 571 and 578), and the rest have been identified on the basis of molecular docking or crystallography data (119, 120, 123, 194, 195, 198, 200, 201, 202, 207, 208, 378, 568, 569, 575 and 655 to 660).…”
Section: Introductionmentioning
confidence: 99%